Construction of an isokinetic eccentric cycle ergometer for research and training - Elmer, S. J.; Martin, J. C. (Journal of Applied Biomechanics, 2013)
Eccentric cycling serves a useful exercise modality in clinical, research, and sport training settings. However, several constraints can make it difficult to use commercially available eccentric cycle ergometers. In this technical note, we describe the process by which we built an isokinetic eccentric cycle ergometer using exercise equipment modified with commonly available industrial parts. Specifically, we started with a used recumbent cycle ergometer and removed all the original parts leaving only the frame and seat. A 2.2 kW electric motor was attached to a transmission system that was then joined with the ergometer. The motor was controlled using a variable frequency drive, which allowed for control of a wide range of pedaling rates. The ergometer was also equipped with a power measurement device that quantified work, power, and pedaling rate and provided feedback to the individual performing the exercise. With these parts along with some custom fabrication, we were able to construct an isokinetic eccentric cycle ergometer suitable for research and training. This paper offers a guide for those individuals who plan to use eccentric cycle ergometry as an exercise modality and wish to construct their own ergometer.